2014
DOI: 10.1002/jssc.201400037
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun polyamide–polyethylene glycol nanofibers for headspace solid‐phase microextration

Abstract: A solution of polyamide (PA) containing polyethylene glycol (PEG) as a side low-molecular-weight polymer was electrospun. After synthesizing the PA-PEG nanofibers, the constituent was subsequently removed (modified PA) and confirmed by Fourier transform infrared spectroscopy. The scanning electron microscopy images showed an average diameter of 640 and 148 nm for PA and PA-PEG coatings, respectively, while the latter coating structure was more homogeneous and porous. The extraction efficiencies of PA, PA-PEG, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…Analytes desorption and their subsequent determination by GC/MS showed that this nanofibrous sorbent is stable against most of the organic solvents and can be used for more than 200 times to measure pesticides with acceptable analytical parameters. High extraction yields were achieved by Bagheri et al in chlorophenols enrichment using modified electrospun PA nanofibres . In this study, PEG was added to the PA solution to increase the electrical conductivity of the solution and to facilitate PA electrospinnability.…”
Section: Applicationsmentioning
confidence: 97%
See 1 more Smart Citation
“…Analytes desorption and their subsequent determination by GC/MS showed that this nanofibrous sorbent is stable against most of the organic solvents and can be used for more than 200 times to measure pesticides with acceptable analytical parameters. High extraction yields were achieved by Bagheri et al in chlorophenols enrichment using modified electrospun PA nanofibres . In this study, PEG was added to the PA solution to increase the electrical conductivity of the solution and to facilitate PA electrospinnability.…”
Section: Applicationsmentioning
confidence: 97%
“…High extraction yields were achieved by Bagheri et al in chlorophenols enrichment using modified electrospun PA nanofibres. 93 In this study, PEG was added to the PA solution to increase the electrical conductivity of the solution and to facilitate PA electrospinnability. Then, PEG was removed from the nanofibres mat by immersing the nanofibres in water to obtain modified PA nanofibres.…”
Section: Pre-concentration and Measurement Of Pesticides In Crops Andmentioning
confidence: 99%
“…Our study contributes to the fresh technique of making SPME assemblies from nanofibres. First analytically successful preparations of electrospun SPME assemblies were announced few years earlier: in 2012 for polyamide [14]; in 2014 for polyacrylate-polyethylene glycol copolymer (PA-PEG) [15] and for polyetherimide (PEI) [16]. The latter polymer is also the topic of this research.…”
Section: Introductionmentioning
confidence: 99%
“…Nanofibers, as new materials, have drawn attention to research for potential applications in diverse fields, such as biomedical materials and catalysts . Nanofibers have diameters ranging from nanometer to micrometer and a high‐specific surface area, which make them favorable for SPE . The effective interaction between the target compounds and nanofibers could greatly reduce the usage of both the solid phase and desorption solvent, which is more environmentally friendly .…”
Section: Introductionmentioning
confidence: 99%
“…Most of the studies use the different principles of phase separation as the main ways to generate porous structure in organic‐based electrospun porous nanofibers preparation , such as the solvent evaporation induced phase separation , the nonsolvent induced phase separation , the blending electrospinning phase separation , and the copolymer electrospinning phase separation . Electrospun nanofibers are applied in SPE to prepare many kinds of samples and have obtained good performance . But so far, there are few studies focusing on porous eletrospun nanofibers used as an SPE material.…”
Section: Introductionmentioning
confidence: 99%